Do co-ethnic commuters disseminate labor market information? Evidence from geocoded register data - Johan Klaesson; Özge Öner; Dieter Pennerstorfer (Johannes Kepler University of Linz, Department of Economics, 2023)
This article provides causal evidence of the significant role ethnic networks play in facilitating labor market integration by reducing information frictions. Using full population geocoded employer-employee matched Swedish register data, we investigate how co-ethnic commuters can influence the work location of immigrants for their initial employment. We argue that these ethnic peers transmit job specific information from their places of work to fellow ethnic peers within the same residential neighborhood who seek jobs. We find that a new immigrant's likelihood of securing their first job at a certain location increases with the presence of co-ethnic commuters from their residential neighborhood: Each additional commuter of the same ethnic network increases the probability of finding employment in a specific neighborhood by 2.3 %. This effect is more pronounced for women, co-ethnic commuters with similar education levels, and immigrants who land their first jobs in larger firms.
Keywords: F22; J61; J64; O18; R23; 330; Co-ethnic commuters; information frictions; ethnic networks; labor market integration; ethnic enclaves